Clinical utility of panel-based genetic sequencing for von Willebrand disease - Radha Ramanan; Christine Van Laer; Sarissa Baert; Cyrielle Kint; Chris Van Geet; Quentin Van Thillo; Peter Verhamme; Thomas Vanassche; James D. McFadyen; Andrew C. Perkins; Huyen A. Tran; Veerle Labarque; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: von Willebrand disease (VWD) is the most prevalent inherited bleeding disorder with a wide spectrum of causative variants. Next-generation sequencing analyzes the entire VWF gene and provides concomitant assessment of other genes, allowing differentiation between genocopies. Objectives: We aimed to assess the clinical impact of panel-based sequencing in all VWD patients sequenced at UZ Leuven. Methods: We conducted a single-center retrospective study of all patients with confirmed or suspected VWD who were screened with panel-based whole-exome sequencing. Presequencing diagnosis was performed using laboratory measures of VWF activity and quantity. Postsequencing diagnosis was informed by variant curation in combination with laboratory measures. We measured clinically meaningful changes in the pre- vs postgenetic sequencing diagnosis and subtyping. Results: The study included 108 patients. The population was predominantly composed of pediatric patients <18 years old (77/108; 71%) and females (66/108; 61%). The largest presequencing subgroup was those with low VWF (61/108; 56%), followed by type 1 VWD (21/108; 19%) and type 2 not otherwise specified (18/108; 17%). A clinically meaningful change in management occurred in 19% (20/108) of the study population. The largest effect was seen in the presequencing type 2 group (16/24; 67%). In the type 2 group who could not be accurately subtyped into 2A/B/M/N prior to sequencing (type 2 not otherwise specified), 15/18 (83%) were able to be subtyped or given a different diagnosis postsequencing. Conclusion: Panel-based sequencing for VWD in a well-selected cohort, particularly those with type 2 and type 3 VWD, was clinically relevant in differentiating genocopies, directing therapies, and family planning. Sequencing in those with low VWF and type 1 VWD rarely changed management.